2010
DOI: 10.1111/j.1095-8312.2010.01384.x
|View full text |Cite
|
Sign up to set email alerts
|

Red anemone guild flowers as focal places for mating and feeding by Levant glaphyrid beetles

Abstract: Several species of glaphyrid (Scarabaeoidea: Glaphyridae) beetles forage and mate on Mediterranean red bowlshaped flowers. In red anemones and poppies in Israel, female beetles occupy only a subset of the flowers, do not aggregate, and are hidden below the petals. This raises the question of how males find their mates. In the present study, we investigated the hypothesis that males and females orient to similar plant-generated cues, thereby increasing their mate encounter prospects. Previous studies have demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…The role of dark flower center in the pollination system of L. pubescens was not revealed here. Several studies have examined the role of central dark-color spot in flowers (Dafni et al, 1990;Eisikowitch, 1980;Johnson & Midgley, 1997;Keasar et al, 2010;Lamborn & Ollerton, 2000) but to date, there is no clear explanation for their adaptive role. In L. pubescens, both dark and light flowers had similar fitness, and overall visit frequencies were not different between tube-color morphs.…”
Section: Flower Diametermentioning
confidence: 99%
See 1 more Smart Citation
“…The role of dark flower center in the pollination system of L. pubescens was not revealed here. Several studies have examined the role of central dark-color spot in flowers (Dafni et al, 1990;Eisikowitch, 1980;Johnson & Midgley, 1997;Keasar et al, 2010;Lamborn & Ollerton, 2000) but to date, there is no clear explanation for their adaptive role. In L. pubescens, both dark and light flowers had similar fitness, and overall visit frequencies were not different between tube-color morphs.…”
Section: Flower Diametermentioning
confidence: 99%
“…A dark flower center was proposed to play a role in attracting pollinators as an orientation mark toward the location of both reproductive organs and reward (e.g., Dafni et al, 1990;Ellis & Johnson, 2010;Ellis et al, 2014;de Jager & Ellis, 2012Johnson & Dafni, 1998;Johnson & Midgley, 1997Keasar et al, 2010;Papiorek et al, 2016). Darwin (1888) proposed that a dark flower center is of no functional importance to the plant and it may reflect past adaptation that is not functioning in present environment.…”
Section: Introductionmentioning
confidence: 99%
“…In the east Mediterranean region, the phenology of glaphyrid beetles and red flowers overlaps in a temporal succession of species that conserve this mode of plant-pollinator interaction (Dafni et al 1990). While beetles mediate the reproduction of the plants, flowers provide food resource, mating site and shelter for the beetles (Keasar et al 2010) (Fig. 1).…”
Section: Ecological and Evolutionary Implicationsmentioning
confidence: 99%
“…It has been observed that glaphyrid beetles tend to visit red flowers almost exclusively when they are present (Tamar Keasar and Avi Shmida personal observations). Colored trap experiments indicate that red coloration alone would explain this preference (Dafni et al 1990;Keasar et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…But flowers are also mating sites for insects (Thornhill & Alcock, ; Barth, ). This is the case for many species of Glaphyridae, whose adults feed on floral pollen and mate on flowers (Keasar et al ., ). Several species of these beetles rely strongly on visual cues to find particular flowers, as receptive females on flowers are highly dispersed in space and to find them may be difficult for males, especially if the density of females is lower than that of flowers.…”
Section: Introductionmentioning
confidence: 97%